Nanoemulsions as Encapsulation System to Prevent Lipid Oxidation - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Springer International Publishing, 2022)
Nanoemulsions consist of small droplets (typically with a diameter <200 nm) dispersed in a continuous phase, where emulsifier molecules surround each droplet. They have great potential in the food industry for encapsulating, protecting, and delivering lipid compounds in order to improve the quality, bioaccessibility, and shelf life of food products, nutritional supplements, and nutraceuticals. Nanoemulsions present several advantages compared to conventional emulsions, such as good dispersibility in water, clarity, kinetical stability, and a greater lipid bioaccessibility, being an excellent carrier for lipid bioactive compounds in food applications. Besides, they can be designed to have different optical, rheological, and chemical properties when controlling their composition and structure. In this context, this chapter is focuses on nano-emulsification as a tool to improve the oxidative stability of lipid bioactive compounds incorporated into them, where diverse strategies to prevent lipid oxidation will be addressed. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.